PERANCANGAN UI/UX VAPEJIE.ID BERBASIS WEBSITE DENGAN METODE DESIGN THINKING PADA LAYANAN POINT OF SALE (POS) - jihad paratama jiat; MUHAMMAD JIHAD PRATAMA SUMAILA (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The growth of the e-cigarette (vape) industry in Indonesia has driven the need for an efficient operational management system, particularly through the use of website-based Point of Sale (POS). However, existing POS systems still face issues with their interface and user experience (UI/UX) which are less intuitive, hindering transaction processes and inventory management at VapeJie.id stores. This study aims to design a user-centered UI/UX for a website-based POS system using the Design Thinking method. This method includes five stages: empathize, define, ideate, prototype, and test. Data collection was conducted through observation and in-depth interviews to identify user problems and needs, such as navigation complexity due to high product variety. Based on the analysis, a POS system prototype was designed that emphasized ease of use, efficient vaporista workflow, and real-time inventory management. The developed prototype was then tested using the system usability scale (SUS) method to evaluate the effectiveness and efficiency of the design. The results of the usability testing system showed a test result of 90%, categorized as excellent, indicating that the resulting UI/UX design is able to improve transaction process efficiency and simplify product stock management. This study concludes that the application of the Design Thinking method is effective in producing a POS system design that is functional, adaptive, and in accordance with the characteristics of the vape industry, and contributes to the development of a user-oriented retail management system.